Principles and Rules of the Analysis of the Single Words of the Quran in the View of The Qamus of the Quran - Mohammad ali Mahdavirad; Seyyed Mohammad Musavi Moqaddam; Motahhare sadat Tayyeb hosseini (مطالعات زبانی و بلاغی)
Understanding the single words of the Holy Quran depends on principles and rules, knowing and explanation of which paves the way for better understanding of the meaning of the words and ultimately facilitates reaching the divine purpose of the verses. One of the good works in the area of exegesis of the single words of the Quran is The Qamus of the Quran by Seyyed 'Ali Akbar Qorashi. Using a descriptive-analytical method, the present article explores the principles and rules of lexicology of the Quran from the viewpoint of The Qamus of the Quran. The extracted samples have been selected randomly. Studying the book and discovering and examining the principles and rules used by the author, it is understood that the author has systematically explained the words of the Quran with the use of various authentic works and based on clear principles and rules. The book is comprehensiveness in explanation and description of the matters. The author’s method of analyzing the single words maintains a thriving spirit in research and criticism, which is one of the most important reasons for reaching remarkable innovations in this regard.